Investigating the effects of general perceived inequality on appetite - Low, Xenia Jia Hui (2019)
Economically unequal societies have higher obesity rates than societies which are more equal. Within societies, studies have found higher risk for obesity to be evident across the whole social gradient. Previous research suggested that financial resources were closely linked to food resources, and that perceived scarcity resulted in increased food intake. More recently, it was found that the perception of high levels of inequality in one’s society led individuals to view their normative climate as more competitive. Given that a competitive environment stimulates high food intake, I proposed that high general perceived inequality would result in an increase in appetite. I tested this hypothesis through two experiments by manipulating participants’ perceptions of inequality in a hypothetical society. Experiment 1 measured appetite through a computerised portion selection task while experiment 2 measured appetite though an ad-libitum consumption task disguised as a taste test. No significant results were found regarding the relationship between general perceived inequality and appetite. However, high general perceived inequality led to an increase in negative affect, although further mediation analyses produced no significant results. Several factors that could have affected the results, including methodological limitations and other possible mechanisms, were discussed. Although no significant results were found, the relationship between general perceived inequality and appetite should continue being researched, given that obesity is an increasing cause for concern and that economic inequality seems to have vast health consequences.